2020
DOI: 10.1055/a-1270-2100
|View full text |Cite
|
Sign up to set email alerts
|

Barrieren und Ressourcen in der Behandlung von Patient/innen mit Migrationshintergrund in der psychosomatischen Rehabilitation

Abstract: ZusammenfassungPatient/innen mit Migrationshintergrund nehmen Angebote der psychosomatischen Rehabilitation seltener in Anspruch und erreichen niedrigere Behandlungserfolge als Patient/innen ohne Migrationshintergrund. In der Gesundheitsversorgung begegnen Patient/innen mit Migrationshintergrund verschiedenen Prozessbarrieren und individuellen Hindernissen, die die Behandlung erschweren können. Studien haben gezeigt, dass auch für Mitarbeiter/innen in Gesundheitseinrichtungen die Behandlung von Patient/innen m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Yet there are few studies which investigate the successful interventions used, and even fewer which use a controlled methodology allowing us to draw conclusions about their effectiveness. This comprehensive scoping review has shown, however, that commonly used therapies include psychopharmacology (Hinton et al, 2012;Sonne et al, 2016;Strømme et al, 2020), culturally informed care or treatment for depression (Bhogal, 2020;Lee, 2015;Wolf et al, 2017), psychological therapy (Reich et al, 2015;Sambucini et al, 2020;Weber et al, 2020), inpatient care (Anderson et al, 2021;Handtke et al, 2021;Schaffrath et al, 2017), and culturally adapted CBT (Hinton & Jalal, 2019;Jalal et al, 2018;Kananian et al, 2020). The authors have noted, however, a paucity in comprehensive psychological assessment and interventions for individuals seeking refuge and asylum and highlight the need for a culturally informed psychological assessment, formulation, treatment plan and intervention for each individual who may be experiencing embodied trauma, from a humanistic, person-centered (Rogers, 1951(Rogers, , 1957a(Rogers, , 1957b(Rogers, , 1959(Rogers, , 1961(Rogers, , 1963, psychosocial (Bailey et al, 2021;Hocking, 2021;Schmalbach et al, 2021), and transcultural perspective (Charura & Lago, 2021;Zahid, 2021).…”
Section: Key Therapeutic Interventionsmentioning
confidence: 99%
“…Yet there are few studies which investigate the successful interventions used, and even fewer which use a controlled methodology allowing us to draw conclusions about their effectiveness. This comprehensive scoping review has shown, however, that commonly used therapies include psychopharmacology (Hinton et al, 2012;Sonne et al, 2016;Strømme et al, 2020), culturally informed care or treatment for depression (Bhogal, 2020;Lee, 2015;Wolf et al, 2017), psychological therapy (Reich et al, 2015;Sambucini et al, 2020;Weber et al, 2020), inpatient care (Anderson et al, 2021;Handtke et al, 2021;Schaffrath et al, 2017), and culturally adapted CBT (Hinton & Jalal, 2019;Jalal et al, 2018;Kananian et al, 2020). The authors have noted, however, a paucity in comprehensive psychological assessment and interventions for individuals seeking refuge and asylum and highlight the need for a culturally informed psychological assessment, formulation, treatment plan and intervention for each individual who may be experiencing embodied trauma, from a humanistic, person-centered (Rogers, 1951(Rogers, , 1957a(Rogers, , 1957b(Rogers, , 1959(Rogers, , 1961(Rogers, , 1963, psychosocial (Bailey et al, 2021;Hocking, 2021;Schmalbach et al, 2021), and transcultural perspective (Charura & Lago, 2021;Zahid, 2021).…”
Section: Key Therapeutic Interventionsmentioning
confidence: 99%